Resistance towards metronidazole in Blastocystis sp.: A pathogenic consequence - Rajamanikam, Arutchelvan; Ho, Shiaw Hooi; Kudva, Madhav; Samudi, Chandramathi; Kumar, Suresh (Public Library of Science, 2019)
Blastocsytis sp. is a protozoan parasite that has been linked to common gastrointestinal illnesses. Metronidazole, the first line therapy, was reported to show frequent inefficacy. Previously, Blastocystis sp. isolated from different population showed varying metronidazole resistance. However, the effect of metronidazole treatment on pathogenic potentials of Blastocystis sp. isolated from different populations, which is known to have different gut environment, is unclear. This study investigates the in vitro effect of metronidazole on the pathogenic potentials of Blastocystis sp. isolated from urban and orang asli individuals. Blastocystis sp. ST 3 isolated from symptomatic and asymptomatic individuals were treated with a range of metronidazole concentration. The parasites’ growth characteristics, apoptotic rate, specific protease activity and the ability to proliferate cancer cells were analyzed upon treatment with 0.001 mg/l metronidazole. The study demonstrates that Blastocystis sp. isolates showed increase in the parasite numbers especially the amoebic forms (only in urban isolates) after treating with metronidazole at the concentration of 0.001 mg/ml. High number of cells in post-treated isolates coincided with increase of apoptosis. There was a significant increase in cysteine protease of Blastocystis sp. isolates upon treatment despite the initial predominance of serine protease in asymptomatic isolates. Metronidazole resistant Blastocystis sp. also showed significant increase in cancer cell proliferation. Resistance to metronidazole did not show significant different influence on the pathogenicity between Blastocystis sp. isolated from urban and orang asli individual. However, an increase in parasite numbers, higher amoebic forms, cysteine protease and ability to proliferate cancer cells implicates a pathogenic role. The study provides evidence for the first time, the effect of metronidazole towards enhancing pathogenic potentials in Blastocystis sp. when isolated from different gut environment. This necessitates the need for reassessment of metronidazole treatment modalities. © 2019 Rajamanikam et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.